P2P video streaming combining SVC and MDC - López-Fuentes, Francisco de Asís (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we propose and evaluate a combined SVC-MDC (Scalable Video Coding & Multiple Description Video Coding) video coding scheme for Peer-to-Peer (P2P) video multicast. The proposed scheme is based on a full cooperation established between the peer sites, which contribute their upload capacity during video distribution. The source site splits the video content into many small blocks and assigns each block to a single peer for redistribution. Our solution is implemented in a fully meshed P2P network in which peers are connected to each other via UDP (User Datagram Protocol) links
Keywords: peer-to-peer networks; video streaming; scalable video coding; multiple description video coding